Fetal brain activity demonstrated by functional magnetic resonance imaging. - Hykin, J; Moore, R; Duncan, K; Clare, S; Baker, P; Johnson, I; Bowtell, R; Mansfield, P; Gowland, P (1999)
Functional magnetic resonance imaging was used to study fetal brain activity. This activity was in response to an auditory stimulus.